Acute urinary retention by fungus balls of Candida. Issue 8 (23rd August 2021) - Anan, Go; Sato, Makoto
Abstract: In the cases of rapid obstruction of urethral catheter, resulting in urinary retention, due to excessive floating material, such as a large number of spherical masses, fungus balls of Candida may be present. Abstract : In the cases of rapid obstruction of urethral catheter, resulting in urinary retention, due to excessive floating material, such as a large number of spherical masses, fungus balls of Candida may be present.